2013
DOI: 10.1080/08941920.2013.847998
|View full text |Cite
|
Sign up to set email alerts
|

Paving the Way for Social Learning When Governance Is Weak: Supporting Dialogue Between Stakeholders to Face a Groundwater Crisis in Morocco

Abstract: Approaches to improve the governance of social-ecological systems are difficult to define in situations where governance is weak, i.e., those involving limited interactions between the actors, and weak management of natural resources. This paper analyzes an action research process implemented in the Chaouia coastal region of Morocco, where weak governance of the social-ecological system led to a groundwater and agricultural crisis. A dialogue between local actors was set up with the aim of identifying strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…In nondemocracies, Kellert et al [33] identify fewer efforts to integrate local knowledge in Kenya and Nepal compared to the United States. Faysse et al's study in Morocco [34] found mutual learning between public staff and farmers, but only about interests and not about managerial problems. In a study of learning in democracies and a nondemocracy, Rist et al [35] detected that state actors inhibit the participation of other stakeholders in democracies as well as in nondemocracies.…”
Section: Learning and Context In Natural Resource Managementmentioning
confidence: 99%
“…In nondemocracies, Kellert et al [33] identify fewer efforts to integrate local knowledge in Kenya and Nepal compared to the United States. Faysse et al's study in Morocco [34] found mutual learning between public staff and farmers, but only about interests and not about managerial problems. In a study of learning in democracies and a nondemocracy, Rist et al [35] detected that state actors inhibit the participation of other stakeholders in democracies as well as in nondemocracies.…”
Section: Learning and Context In Natural Resource Managementmentioning
confidence: 99%
“…Westoby (2014) articulates a rationale for the relevance of There is precedence for this value of social learning in dialogue. Faysse et al (2014), for example, highlight the value of collaborative, social learning that resulted from dialogue processes regarding agricultural issues, particularly in bridging differences between stakeholders with opposing views. Similarly, in an agricultural context in western Africa, Akpo, Crane, Vissoh, and Tossou (2015) report on multistakeholder processes including dialogue that encouraged social learning by incorporating the areas of knowledge of different stakeholders in a way that resulted in co-ownership of project outcomes among initially disparate groups.…”
Section: A Model Of Learning Dialoguementioning
confidence: 99%
“…Faysse, Nicolas, Mostafa, Amar, and Hassane (2014), for example, describe an action research process in…”
Section: The Rise Of Dialogue In Stakeholder Engagementmentioning
confidence: 99%
“…The review shows that the factors and conditions that enable or constrain adaptation to climate change are very context specific, dynamic, and not easily captured (Faysse et al, 2014). In many Western democracies, climate change is seen as the key driver of vulnerability, and policy intervention strategies are mostly intended to deal with projected climate change impacts.…”
mentioning
confidence: 99%
“…Crosslevel and horizontal networks create new opportunities for diverse actors to participate in decision making and to engage in mutual learning (Pahl-Wostl, 2009). Social learning may thus inform approaches aimed at reinforcing multilevel governance in places where governance is emergent (Faysse et al, 2014), as is the case in Vietnam.…”
mentioning
confidence: 99%